MEMBANGUN DESA MELALUI PENDIDIKAN EKONOMI PENGELOLAAN SUMBER DAYA ALAM LINGKUNGAN UNTUK MEWUJUDKAN DESA YANG TERINTEGRASI - Karolina Albina Rewa; Rivaldy Umbu Tamu Takandjandji; Fredik Ndawa Takanjanji; Aprilianto Aprilo Pali Kadata; Bravo Elsahaddai Pratu; Erwin Danga Ngara; Haryono Umbu Hina Kapita; Fitriyanti Ata Luda; Upa Waja; Indrayanto Umbu Yaka; Susanti Tamu Ina; Santi Lemba Hunggu Hamu; Margareta Kani Habar; Desnawati Inga Lika; Richard Aprianto Umbu Lili; Fenti Yodiansi Kristin Hermanus (Yayasan Nusa Cendekia Global, 2026)
Real Work Lecture (KKN) is a form of student service to the community to develop the knowledge gained during lectures on campus. The Real Work Lecture for integrated entrepreneurial villages will be held on June 21, 2025 - August 09, 2025. The KKN program is a vehicle for training and learning for KKN students but is also part of the efforts of Wira Wacana Sumba Christian University in contributing to transforming the values of education, care, and leadership to the community. In carrying out the program, KKN students are accompanied by field supervisors (DPL). It is hoped that it can have a positive impact on the community of the Uta Pambapang preparatory village and for students in elementary schools, teachers and the general public of the Uta Pambapang preparatory village as well as KKN students as the implementation of the preparation of activities in the Uta Pambapang preparatory village, Lewa District, East Sumba Regency, East Nusa Tenggara Province.